2021
DOI: 10.1016/j.idh.2020.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Air travel in a COVID-19 world: Commercial airline passengers’ health concerns and attitudes towards infection prevention and disease control measures

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 20 publications
4
28
1
1
Order By: Relevance
“… Dzisi and Dei (2020) examined the compliance to the policy on facemasks in public transportation, suggesting willingness to comply to the social distancing guidelines while the facemask policy was followed only partially. Only one study examined airline passengers’ health concerns and attitudes toward protective measures in COVID-19 ( Sotomayor-Castillo et al, 2021 ). One of the findings related to mask use suggested that, compared to the use of sanitary measures, fewer respondents were willing to wear a mask even it was provided by their preferred airline.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Dzisi and Dei (2020) examined the compliance to the policy on facemasks in public transportation, suggesting willingness to comply to the social distancing guidelines while the facemask policy was followed only partially. Only one study examined airline passengers’ health concerns and attitudes toward protective measures in COVID-19 ( Sotomayor-Castillo et al, 2021 ). One of the findings related to mask use suggested that, compared to the use of sanitary measures, fewer respondents were willing to wear a mask even it was provided by their preferred airline.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, providing hygiene necessities and maintaining hygiene standards at airports has been one of the top priorities for passengers [7,88,89]. To lessen travel concerns, the literature has discussed the importance of providing complimentary hand sanitizers, sanitary wipes, and masks to passengers [90]. As a result, this finding can be explained by the growing concern over hygiene and cleaning caused by COVID-19 pandemic.…”
Section: Complementary Analysis For Post-covid-19 Periodmentioning
confidence: 99%
“…The Korea Airport Corporation ( KAC; 2020a ) surveyed 1000 people on their willingness to travel abroad in May 2020 and found that 60% of the respondents did not intend to use air transportation until the development of medicines and vaccines. In this situation, rebuilding consumer confidence and reducing perceived threats are key to the recovery of air passenger travel ( Lamb et al, 2020 ; Sotomayor-Castillo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%